NMR transverse relaxation of the clay-rich shale in inhomogeneous magnetic field: A numerical study. (September 2022) - Ge, Xinmin; Zhang, Renxia; Liu, Jianyu; Fan, Yiren; Zhao, Jier; Li, Chaoliu; Hu, Falong
Abstract: We conducted comprehensive numerical simulations to probe the low field nuclear magnetic resonance (NMR) relaxation of the clay-rich shale in inhomogeneous magnetic field. Under the guidance of the Bloch equation, the relaxation property of a unimodal distributed clay-rich shale is simulated using the Carr-Purcell-Meiboom-Gill (CPMG) pulse sequence. Both the magnetization and the transverse relaxation time (T2 ) spectrum are obtained to investigate influential factors such as the excitation pulse angle, the refocusing pulse angle, the pulse duration, the echo spacing, as well as the off-resonance frequency. The simulation result showed that the field inhomogeneity contributes great influence on the NMR relaxation, particular in high magnetic field strength and high off-resonance frequency. We observed that in standard CMPG pulse sequence, the amplitude of the T2 distribution is negatively correlated with the off-resonance frequency and can be compensated by the empirical regression. Moreover, the excitation pulse angle poses great impact on the amplitude of the T2 distribution, but has less influence on the T2 distribution and its peak value. On the contrary, both the amplitude and the peak value of the T2 spectrums are also impacted by the refocusing pulse angle, especially in higher magnetic field inhomogeneity. The refocusing pulse angle is preferable higher than 150° for the clay-rich shale since it helps the spins to rephrase quickly. In additional, the echo spacing is ideally reduced to as low as its minimal value for the measurement of samples with short relaxation component. The result provides comprehensive knowledge on influential factors of the NMR relaxation of the clay-rich shale, which is useful for the optimization of the pulse sequence, the acquisition conditions, as well as the manipulation of the magnetization data. Highlights: The magnetization evolution is developed by the matrix rotation method. NMR responses of the tight sand at representative magnetic fields are simulated. Joint effect of the field inhomogeneity and the pulse sequence are investigated.